"A decent man, but not very popular": JGN Strauss, the United Party and the founding of the apartheid state, 1950-1956 - Mouton, F. A. (Faculty of Humanities, University of the Free State, 2013)
JGN Strauss, leader of the United Party and the official parliamentary opposition between 1950 and 1956, was a flawed politician. His aloofness and inability to suffer fools meant that he lacked the popular touch, making it impossible for him to gain popularity. And yet, he never lacked courage and integrity. He was appalled by the ruthlessness of the National Party, especially its disregard for the rule of law and the entrenched clauses in the constitution protecting the Coloured franchise on the common voters roll, in creating the apartheid state. Against the wishes of a significant section in his own party he confronted the NP on these issues. A palace revolution in November 1956 led to his removal as leader of the opposition. And yet, despite the humiliating end to his political career, and the subsequent perception that he was a failure, Strauss was a shrewd and able politician who under challenging circumstances profoundly influenced white parliamentary politics.
Keywords: JGN Strauss; United Party; Coloured franchise; Constitution; National Party; Apartheid; Progressives; Sir De Villiers Graaff